Leadership Styles and Psychological Empowerment: A Meta-Analysis. (February 2022) - Schermuly, Carsten C.; Creon, Laura; Gerlach, Philipp; Graßmann, Carolin; Koch, Jan
Psychological empowerment has become a popular construct in organizational research and practice. Leadership ranks high among the best predictors of employees' psychological empowerment, yet little is known about which leadership styles prove more effective than others. This meta-analysis investigates the effects of four leadership styles on psychological empowerment. More specifically, we test whether empowering leadership evokes more psychological empowerment than transformational leadership, servant leadership, or transactional leadership. We found that empowering, transformational and servant leadership contribute almost equally to psychological empowerment. No relationship was found with transactional leadership. In an explorative manner, we tested the effects on the different dimensions of psychological empowerment. We found that the leadership styles had a weaker influence on the competence dimension of psychological empowerment. We also investigated the effects of several moderators on the relationships with psychological empowerment: country culture (power balanced freedom (PBF)), study design (cross-sectional vs. multi-wave studies) and publication status (published vs. unpublished). We found no moderating effects of culture, which indicates the universally empowering effects of the leadership styles. The relationships between leadership and empowerment were somewhat weaker when data were collected at different measurement points, and publication bias does not seem to be an issue in this research field.